Motivation for Education at the Primary, Secondary and Tertiary Health Care (Journal of Universal Excellence, 2026)
Research Question (RQ): There is a difference in motivation for education among healthcare providers according to the level of health care.Purpose: The purpose of the research was to present the concepts of education in health care, healthcare and to examine the motivation for educating health workers at the primary, secondary and tertiary level of health.Method: The method that we will use will be a qualitative, descriptive approach based on the study of existing literature, articles, and personal experiences.Results: In the study, we concluded that continuous education is the key to the professional development of an individual. In today's time, continuous tracking of medicine and medicine is inevitable for all those employed in health care, but this can be achieved through continuous education. So that we have concluded that, there is no difference between motivations for education among healthcare providers according to the level of health care. The introduction puts forward the thesis namely: We can confirm there is a difference among healthcare providers according to the level of health care in motivation for education.Organization: The impact of research on public health is great because healthcare providers through education raise their effectiveness in work processes and, consequently, in the whole organization.Society: Education positively influences the quality treatment of health care consumers.Originality: On the basis of a transparent article, the management of health institutions can produce an Index of motivation for education in health care.Limitations/Future Research: The research was based on domestic and foreign literature and articles.
Keywords: health; health workers; healthcare; motivation for education; patient; competence; professionalism; lifelong learning